Centimeter‐Height 3D Printing with Femtosecond Laser Two‐Photon Polymerization. Issue 5 (19th February 2018) - Chu, Wei; Tan, Yuanxin; Wang, Peng; Xu, Jian; Li, Wenbo; Qi, Jia; Cheng, Ya
Abstract: Nowadays 3D printing has been widely used for producing geometrically complex 3D structures from a broad range of materials such as ceramics, metals, polymers and semiconductors. Although it has been demonstrated that a fabrication resolution as high as ≈100 nm can be achieved in 3D printing based on two‐photon polymerization (TPP), the end product height of TPP is typically on millimeter scale limited by the short working distance of high‐numerical‐aperture focal lens. Herein, a method based on simultaneous spatiotemporal focusing of the femtosecond laser pulses is presented, which enables fabricating centimeter‐height 3D structures of fine features with TPP. An isotropic spatial resolution is also demonstrated, which can be continuously tuned in the range of ≈10–40 µm by only varying the power of femtosecond laser, making this technique extremely flexible and easy to implement. Several Chinese guardian lions of a maximum height of 0.6 cm and a Terra Cotta Warrior of a height of 1.3 cm are fabricated using this method. Abstract : A technique for printing 3D fine structures of large heights and high spatial resolutions is established. An identical resolution of ≈10 µm in XYZ directions is achieved by resolving the issue of large focal depth inherently associated with low numerical apertures. High‐resolution printing of 3D sculptures is demonstrated.